Influences of Cognitive Processing Capacities on Speech Perception in Young Adults - Tao, Lily; Taft, Marcus (Frontiers in Psychology, 2017)
Foreign accent in speech often presents listeners with challenging listening conditions. As such, listeners may need to draw on additional cognitive resources in order to perceive and comprehend such speech. Previous research has shown that, for older adults, executive functions predicted perception of speech material spoken in a novel, artificially created (and therefore unfamiliar) accent. The present study investigates the influences of executive functions, information processing speed, and working memory on perception of unfamiliar foreign accented speech, in healthy young adults. The results showed that the executive processes of inhibition and switching, as well as information processing speed predict response times to both accented and standard sentence stimuli, while inhibition and information processing speed predict speed of responding to accented word stimuli. Inhibition and switching further predict accuracy in responding to accented word and standard sentence stimuli that has increased processing demand (i.e., nonwords and sentences with unexpected semantic content). These findings suggest that stronger abilities in aspects of cognitive functioning may be helpful for matching variable pronunciations of speech sounds to stored representations, for example by being able to manage the activation of incorrect competing representations and shifting to other possible matches.